Karakteristik Klinis Dermatitis Atopik di RS Muhammadiyah Bandung Tahun 2020-2022 - Natasya Artha Putri; Mia Yasmina Andrarini; Lisa Adhia Garina (Jurnal Riset Kedokteran, 2024)
Abstract. The incidence of Atopic Dermatitis (AD) is a big problem, especially in developing countries. Data on the incidence of AD in Indonesia is still not clearly recorded. Dermatitis is skin inflammation in response to the influence of exogenous and endogenous factors which causes clinical symptoms in the form of efflorescence and complaints of itching. This study aims to determine the number of patients and clinical characteristics of AD at Muhammadiyah Hospital Bandung in 2020-2022. The aim of this study was to determine the clinical characteristics of atopic dermatitis in RSMB in 2020-2022. This method uses descriptive observational with a cross-sectional retrospective approach. The study population consisted of all AD sufferers, with a total of 146 patients taken from medical records, 88 patients with confirmed AD. The research results showed a decrease in the incidence of DA in 2020-2022. DA increased in children aged 2-16 years (43.2%). The female gender is more numerous (55.6%). The most common occupation is students (40.9%). The most common lesion location in children was in the flexural folds of the lower extremities (44.8%). The most common accompanying diagnosis was non-specific dermatitis (4.54%). The most common treatment was topical corticosteroids (57.9%). The conclusion is that the incidence of DA will decrease in 2020-2022. DA increases in the pediatric age group. There are more women. Most students work. The most common lesion locations are in the flexural folds of the lower extremities. The most common concomitant diagnosis is non-specific dermatitis. The most common treatment is topical corticosteroids. Abstrak. Kejadian Dermatitis Atopik (DA) merupakan masalah besar khususnya di negara berkembang. Data kejadian DA di indonesia masih belum terdata jelas. Dermatitis merupakan peradangan kulit sebagai respon terhadap pengaruh faktor eksogen dan faktor endogen yang menimbulkan kelainan klinis berupa efloresensi dan keluhan gatal. Penelitian ini bertujuan untuk mengetahui jumlah pasien dan karakteristik klinis DA di RS Muhammadiyah Bandung tahun 2020-2022. Tujuan penelitian ini untuk mengetahui karakteristik klinis dermatitis atopik di RSMB tahun 2020-2022. Metode ini menggunakan deskriptif observasional dengan pendekatan retrospektif cross-sectional. Populasi penelitian seluruh penderita DA dengan jumlah 146 pasien diambil dari rekam medis didapatkan 88 pasien terkonfirmasi DA. Hasil penelitian terjadi penurunan angka kejadian DA tahun 2020-2022. DA meningkat pada anak 2-16 tahun (43.2%). Jenis kelamin perempuan lebih banyak (55.6%). Pekerjaan paling banyak yaitu pelajar (40.9%). Lokasi lesi paling banyak pada anak di lipatan fleksural ekstremitas inferior (44.8%). Diagnosis penyerta paling banyak yaitu dermatitis non-spesifik (4.54%). Pengobatan yang paling banyak yaitu kortikosteroid topikal (57.9%). Kesimpulan in bahwa kejadian DA mengalami penurunan pada tahun 2020-2022. DA meningkat pada kelompok usia anak-anak. Jenis kelamin perempuan lebih banyak. Pekerjaan paling banyak pelajar. Lokasi lesi terbanyak di daerah lipatan fleksural ekstremitas inferior. Diagnosis penyerta paling banyak dermatitis non-spesifik. Pengobatan paling banyak kortikosteroid topikal.